2016
DOI: 10.1097/md.0000000000005203
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome in lung cancer with a second malignancy

Abstract: The aim of the study was to determine the clinical outcome of lung cancer patients with a secondary malignancy according to the time sequence between the lung cancer and the secondary malignancy.Retrospective review of all lung cancer patients with any secondary cancer treated from June 2004 to July 2012. The survival of patients with a secondary malignancy was compared to those patients without a secondary malignancy. According to the time sequence between the lung cancer and the secondary malignancy, patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
(25 reference statements)
2
4
0
Order By: Relevance
“…The incidence of previous extrapulmonary malignancies in our study was similar to those reported previously (1-22%) (7,8,(18)(19)(20)(21)(22)(23)(24)(25)(26). Corresponding to an increase in the incidence of multiple primary cancers, a surge of 5.7% in lung cancer as a second primary malignancy was also noted between 1988-1992 and 2011-2014 in the United States National Cancer Institute's Surveillance, Epidemiology, and End Results Program (19).…”
Section: Discussionsupporting
confidence: 89%
“…The incidence of previous extrapulmonary malignancies in our study was similar to those reported previously (1-22%) (7,8,(18)(19)(20)(21)(22)(23)(24)(25)(26). Corresponding to an increase in the incidence of multiple primary cancers, a surge of 5.7% in lung cancer as a second primary malignancy was also noted between 1988-1992 and 2011-2014 in the United States National Cancer Institute's Surveillance, Epidemiology, and End Results Program (19).…”
Section: Discussionsupporting
confidence: 89%
“…[ 4 ] Lu et al has reported the median survival was 12 months for second primary lung cancer. [ 14 ] In this study, the median survival was 27 months in patients whose lung cancer was diagnosed in primary hepato-GI clinic, better than the previously reported second primary lung cancer. [ 14 ] We also found that those with diagnosis of second primary lung cancer not in primary hepato-GI clinic had worse clinical outcome (median survival: 10 months) and included more stage III and IV lung cancer.…”
Section: Discussionmentioning
confidence: 61%
“…[ 14 ] In this study, the median survival was 27 months in patients whose lung cancer was diagnosed in primary hepato-GI clinic, better than the previously reported second primary lung cancer. [ 14 ] We also found that those with diagnosis of second primary lung cancer not in primary hepato-GI clinic had worse clinical outcome (median survival: 10 months) and included more stage III and IV lung cancer. Therefore, as patients survive first cancer, surveillance in clinic may reduce the mortality from second primary malignancies owing to early detection.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations